New Pharmacological Approaches for the Treatment of Neurotrophic Keratitis - Koay, Su Yin; Larkin, Daniel F. P. (Frontiers in Pharmacology, 2022)
Neurotrophic keratitis (NK) is a rare degenerative condition that is caused by damage to the trigeminal nerve, with partial or complete loss of corneal innervation. The loss of sensory innervation leads to impaired healing of corneal epithelium, which subsequently result in punctate epithelial erosions, persistent epithelial defects, corneal ulcers and corneal perforation. Management of NK is often supportive and aims to promote epithelial healing and prevent progression of disease. Multiple novel pharmacological approaches have been proposed to address the underlying pathophysiology of NK, which are discussed in this paper.